This Wonderful Thing - Baron, Adam (London : HarperCollins Children's Books, 2021)
This is a moving and hilarious novel about friendships, family secrets, mystery - and life-changing hidden treasure... Jessica is playing with her family at the river when she finds a dirty, bedraggled teddy bear in the water. She has no idea that it will change everything, forever. Meanwhile, Cymbeline comes home from school to find that his mum's house has been broken into and the thieves seemed oddly focused on his toys. Thank goodness he had Mr Fluffy, his Bear of Most Extreme Importance, with him. Soon, Jessica and Cymbeline find themselves swept up in a mystery that spans decades, threatens their families, and turns their lives upside down. But sometimes, just maybe, a new life can be a really wonderful thing.
"Sometimes you find something that changes everything"--Cover.
Keywords: Friendship -- Juvenile fiction; Family secrets -- Juvenile fiction; Toys -- Juvenile fiction